The Implementation Of Green Purchasing At Conrad Bali Hotel - Ni Putu Tanya; Titien Damayanti; Ni Made Sri Rukmiyati (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the implementation of green purchasing and its implications for operational costs at Conrad Bali Hotel. This topic is important because environmentally friendly procurement practices in the hospitality industry are not only related to compliance with sustainability principles but also closely associated with operational efficiency, supplier selection, and resource-use control. This study employed a qualitative approach, with data collected through interviews, observation, and documentation. The research informants consisted of the Purchasing Manager, Purchasing Supervisor, Cost Control, and Sanitation Hygiene Manager. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Meanwhile, data validity was examined through source triangulation and technique triangulation. The results show that green purchasing at Conrad Bali Hotel has been implemented through supplier selection that considers environmental aspects, the use of reusable packaging, and the application of the reduce and reuse principles in the procurement process. However, its implementation has not been fully optimized due to the limited number of suppliers with ISO 14000 certification, the absence of official green partners, and the incomplete implementation of recycling practices. In terms of cost, environmentally friendly products tend to be more expensive than conventional products. Nevertheless, green purchasing contributes to operational efficiency by reducing waste, decreasing the use of single-use packaging, and strengthening sustainable procurement practices. These findings indicate that green purchasing can serve as an important strategy for supporting environmental sustainability while improving hotel operational efficiency.